10 Researchers Won Medals At IENA And Bio Malaysia Exhibition 2010 - Gupta, Arun
Universiti Malaysia Pahang (UMP) continued to gain success after 10 researchers won two gold medals, four silver medals and four bronze medals at the International Exhibition Ideas - Invention New Products (IENA) 2010 in Germany and Bio Malaysia Exhibition 2010 in Kuala Lumpur recently.